Konsep Al-Tsabit dan Al-Mutahawwil Serta Implikasinya dalam Hukum Islam: Telaah Pemikiran Ali Ahmad Said Asbar - Rokhmad, Abu; Nurdin, Nazar (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
This article examines the concepts of al-tsabit (the unchangeable) and al-mutahawwil (the changeable) which were popularized by Ali Ahmad Said Asbar (Adonis) in Islamic studies, then they are limitedly associated with Islamic legal thinking. This study aims to find a formula for understanding Islamic law that is more comprehensive and dynamic in accordance with the challenges of the times. This paper is a type of qualitative research with a character study approach. The method used is usually qualitative research, but it focuses more on documentation and records of Ali Ahmad Said Asbar's life journey. This study found that the concepts of al-tsabit and al-mutahawwil which were explored deeply by Adonis are important concepts in Islamic studies to be applied in the lives of Muslims. The Koran and al-Sunnah are final with the death of the bearer of the Islamic message. Even so, it is impossible for the two sources of Islamic law to avoid answering legal events that have emerged recently. If its vitality remains, then the jargon of al-Islam â€˜shalih li kulli zaman wa makanâ€™ is not in doubt. This jargon also conveys an important recognition that in Islam there are teachings that are fixed and impossible to change (al-tsabit), and there are also teachings that are dynamic and bound to change (al-mutahawwil). The issue of faith and worship is a principle that cannot change, but in other dimensions of Islam, such as law, it is very likely to be open to new meanings.Â Artikel ini mengkaji tentang konsep al-tsabit (the unchangeable) dan al-mutahawwil (the changeable) yang dipopulerkan oleh Ali Ahmad Said Asbar (Adonis) dalam kajian keislaman, lalu secara terbatas dikaitkan dengan pemikiran hukum Islam. Studi ini hendak menemukan formula pemahaman hukum Islam yang lebih komprehensif dan dinamis sesuai dengan tantangan zaman. Tulisan ini adalah jenis penelitian kualitatif dengan pendekatan studi tokoh. Metode yang dipakai lazimnya penelitian kualitatif, namun lebih fokus pada dokumentasi dan catatan perjalanan hidup Ali Ahmad Said Asbar. Studi ini menemukan bahwa konsep al-tsabit dan al-mutahawwil yang dieksplorasi mendalam oleh Adonis, merupakan konsep penting dalam kajian Islam untuk aplikasikan dalam kehidupan umat Islam. Alquran dan al-Sunnah sudah final seiring dengan wafatnya pembawa risalah Islam. Meskipun begitu, dua sumber hukum Islam tersebut tidak mungkin menghindar untuk menjawab peristiwa-peristiwa hukum yang muncul belakangan. Jika vitalitasnya masih tetap, maka jargon al-Islam shalih li kulli zaman wa makan tidak diragukan. Jargon tersebut sekaligus menyuratkan pengakuan penting bahwa di dalam Islam memang ada ajaran yang tetap dan tidak mungkin berubah (al-tsabit), dan ada pula ajaran yang dinamis dan pasti berubah (al-mutahawwil). Masalah akidah dan ibadah adalah prinsip yang tidak mungkin berubah, namun pada dimensi Islam lainnya, seperti hukum, ia sangat mungkin terbuka menerima makna-makna baru.